Strategies for Strengthening Security in Accounting Information Systems - Mustafa, Firas Mahmood; Salman, Abdulsatar Shaker; Shukur, Mahmood; AL- Nuiami , Sabah Abdul Wahhab Abdul Razaaq (Journal of Ecohumanism, 2024)
Background: As digital transformations reshape the landscape of financial data management, the security of Accounting Information Systems (AIS) has become a top priority. As cyber-attacks become more sophisticated, organisations worldwide have enormous challenges in protecting financial data's integrity, confidentiality, and availability. Objective: The article aims to investigate current risks to AIS security and recommend effective techniques and practices that organisations can follow to improve the security of their accounting information. The emphasis is on reducing the risks associated with cyber threats and maintaining the dependability and accuracy of financial information. Methodology: A thorough literature analysis examined the latest research, reports, and best practices relating to AIS security. In addition, a poll of IT and accounting specialists was undertaken to provide insight into current security concerns and the efficiency of various security methods. Results: The findings show that, while organisations are becoming more conscious of the importance of AIS security, there still needs to be a gap in the deployment of complete security measures. Regular security assessments, encryption technology, cybersecurity awareness training for employees, and integrating advanced threat detection systems have all been mentioned as key initiatives. Conclusion: Improving the security of Accounting Information Systems is critical for protecting sensitive financial data and preserving trust in financial reporting. Organisations must take a multidimensional approach that incorporates technological, procedural, and pedagogical techniques to combat the changing cyber threat landscape